Consequences of Late English Learners - Alfiani, Ika; Agustina, Eliasanti; Setiawan, Rahmat (Universitas Nurul Jadid, 2025)
This study investigates the consequences experienced by late learners and explores how these learners perceive the challenges and benefits throughout their language acquisition journey. Utilizing a sequential explanatory mixed-method approach, quantitative data were gathered from 50 participants via a structured questionnaire and followed by qualitative interviews with four individuals representing early and late English learners. The quantitative findings revealed that late learners frequently face difficulties in grammar, pronunciation, and fluency accompanied by lower self-confidence and declining motivation. These challenges are aligned with the Critical Period Hypothesis (CPH) and Krashen’s Affective Filter Hypothesis, which attribute age and emotional factors as key barriers in second language acquisition. However, qualitative data suggest that strong instrumental motivation, self-directed learning strategies, and the use of digital tools help late learners overcome these limitations. Despite cognitive constraints, age was not the sole determinant of success. Learning outcomes were influenced by learner ability, technological engagement, and environmental support. The study concludes that pedagogical strategies should address both the technical and emotional needs of late learners and suggest policy reform that includes flexible start times, digital resources, and age-appropriate support systems.